Modernisation of the Russian Civil Code: Initial Steps - Musin, Valeriy (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to present initial steps in modernisation of the Civil Code of the Russian Federation. The author presents the selected aspects of the challanges according to the modernisation of the law system in order to answer some substantial economic and social developments that have occured in Russia and should be reflected in civil law regulation.